Nilai Estetika Lokal dan Nilai Ekonomi Lokal Dalam Pengelolaan Destinasi Pariwisata di Bali Utara - Dewa Ayu Diyah Sri Widari; Dewa Putu Oka Prasiasa (Mudra Jurnal Seni Budaya, 2022)
This study aims to find local aesthetic values and local economic values as a result of the interaction of local values and global values in the management of tourism destinations in North Bali. The method used is a literature review method based on qualitative descriptive analysis. The findings of this study are that the element of locality in the management of tourism destinations in North Bali is formed from the embodiment of aesthetic values and local economic values which are believed to be local wisdom of the community, and these two values are dominant. The values brought by tourists can have positive (tonic) and negative (toxic) implications, as well as being a driver of value change for local communities. The contribution of aesthetic value and local economic value to the values brought by tourists has not been optimal in managing tourism destinations in North Bali.